2020
DOI: 10.1055/s-0040-1718384
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Expert Opinion: A Comparison of Antibiotic Regimens for Infectious Urinary Tract Pathology in Pregnancy

Abstract: Objective Outside pregnancy, nitrofurantoin, ciprofloxacin and sulfamethoxazole-trimethoprim (SMZ-TMP) are first-line therapy (FLT) for lower urinary tract infections (LUTIs). Optimal antibiotics for LUTI have been extrapolated based on expert opinion. Progression to pyelonephritis and adverse obstetric outcomes were compared between women who received FLT and those given alternative antibiotics. Methods This study includes a retrospective cohort of women with LUTI, including asymptomatic bacteriuria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In recent years many diseases during pregnancy have been treated using antibiotics [12]; however, the risk of antibiotic exposure during pregnancy is gradually increasing [5]. Researchers have found that the growth of neonates is different from between those treated with and without antibiotics, and there is increasing, but controversial, evidence that exposure to antibiotics during pregnancy might have both short-and long-term effects on babies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years many diseases during pregnancy have been treated using antibiotics [12]; however, the risk of antibiotic exposure during pregnancy is gradually increasing [5]. Researchers have found that the growth of neonates is different from between those treated with and without antibiotics, and there is increasing, but controversial, evidence that exposure to antibiotics during pregnancy might have both short-and long-term effects on babies.…”
Section: Introductionmentioning
confidence: 99%
“…Most infections are caused by Enterobacteriaceae , commonly found in the gastrointestinal tract, with Escherichia coli ( E. coli ) being responsible for 80–90% of cases. However, we can find other bacteria such as Group-B Streptococcus saprophyticus (GBSS), Klebsiella pneumoniae , coagulase-negative Staphylococcus , Staphylococcus aureus and Proteus mirabilis in a lower percentage [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In pregnant women, ASB occurs in an estimated 2–10% [ 7 ], and if left untreated, it can turn into symptomatic AC in 30% of patients and may progress to APN in up to 50% of those patients [ 6 ], which have been associated with several complications for both the mother and the unborn child [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years many diseases during pregnancy have been treated using antibiotics (Krischak et al, 2020); however, the risk of antibiotic exposure during pregnancy is gradually increasing (Dotters-Katz et al, 2020). Researchers have found that the growth of neonates is different from between those treated with and without antibiotics, and there is increasing, but controversial, evidence that exposure to antibiotics during pregnancy might have both short-and long-term effects on babies.…”
Section: Introductionmentioning
confidence: 99%